Computed anatomical modelling of the optic pathway and oculomotor system using magnetic resonance imaging - Juanes, J.A.; Ruisoto, P.; Prats-Galino, A.; Framiñán, A.; Riesco, J.M. (Journal of neuroradiology, 2014)
This study presents a computer-based tool for three-dimensional (3D) visualization of the optic pathway and oculomotor system using 3D high-resolution magnetic resonance imaging (MRI) datasets from a healthy subject. The 3D models were built as wireframe grids co-registered with MRI sections. First, 3D anatomical models were generated of the visual pathway from the eyeball to the primary visual cortex and of the cranial oculomotor nerves from the brain stem to the extrinsic eye muscles. Second, a graphical user interface allowed individual and group visualization, translation, rotation and zooming of the 3D models in different spatial positions simultaneously with MRI orthogonal cut planes. Educational and clinical applications are also discussed.